Concentration of voting rights and board resistance to takeover bids - St-Pierre, Josée; Gagnon, Jean-Marie; Saint-Pierre, Jacques (Journal of Corporate Finance, 1996)
In this paper, we test the hypothesis that the probability of the target's board of directors resisting a takeover bid can be explained by two factors, transaction-specific variables and distribution of voting rights. Our study is conducted in Canada where the distribution of ownership and especially voting rights is more concentrated than in the United States. We find first that some transaction-specific variables are relevant. The past performance of the target, the premium and prior negotiations are negatively associated with the probability of resistance by the managers. Competing bids cause it to increase, but their effect is felt through their interaction with the premium. Given our specific information on prior negotiations, we interpret their effect as unambiguous evidence of risk-reducing behavior on the part of the board. The distribution of voting rights is also relevant: blocks of shares held by the directors are associated with an increase in the probability of resistance. This may be seen as evidence of managerial entrenchment. We document the degree to which these findings differ from those in the United States and seek to explain these differences. Our proxies for board composition are not statistically significant.